Влияние формы распределения частиц по размерам на характеристики переноса излучения - Горячев Б. В. Борис Валентинович; Ларионов В. В. Виталий Васильевич; Могильницкий С. Б. Сергей Борисович; Савельев Б. А.; Новикова Л. А. (Томск, 1991)
Деп. в ВИНИТИ 06.11.91, № 4214-В91